Monitoring of highly active antiretroviral therapy in HIV infection. - Walker, A; Gibb, D (2011)
PURPOSE OF REVIEW: Patients on antiretroviral therapy (ART) in high-income countries have routine laboratory tests to monitor ART efficacy/toxicity. We review studies describing the outcomes and costs of different monitoring approaches, predominantly in low-income countries. RECENT FINDINGS: CD4 cell counts, HIV RNA viral load and clinical events are frequently discordant; viral load suppression occurs with WHO-defined CD4 failure and, as expected, viral load failure often occurs before CD4 failure. Routine CD4 monitoring provides small but significant mortality/morbidity benefits over clinical monitoring, but, at current prices, is not yet cost-effective in many sub-Saharan African countries. Viral load monitoring is less cost-effective with modelling studies reporting variable results. More research into point-of-care tests, methods for targeting monitoring and thresholds for defining failure is needed. Most laboratory monitoring for toxicity is neither effective nor cost-effective. In terms of models for delivery of care, task-shifting with nurse-led and decentralized care appear as effective as doctor-led or centralized care. SUMMARY: Recent studies have improved the evidence base for monitoring on ART. Future research to increase cost-effectiveness by better targeting of monitoring and/or evaluating implementation of less costly point-of-care tests will contribute to long-term success of ART while continuing to increase ART coverage.